Clinical study on high-risk factors for contralateral lymph node metastasis in unilateral papillary thyroid carcinoma - YUAN Xinyue, YAO Yao, CHENG Shuai, ZHENG Xin, ZHANG Yuan (Zhongguo aizheng zazhi, 2023)
Background and purpose: The occurrence of lymph node metastasis in papillary thyroid cancer (PTC) can have adverse effects on the prognosis of patients. This study aimed to investigate risk factors related to the occurrence of contralateral central lymph node metastases (CLNM) and contralateral lateral lymph node metastases (LLNM) when imaging suspected ipsilateral LLNM in unilateral PTC. Methods: We retrospectively analyzed the clinical data of 526 patients who received surgical treatment in the same treatment group of Jiangsu Cancer Hospital Head and Neck Surgery Department from January 2011 to December 2021. They were initially treated with total thyroidectomy and bilateral central lymph node dissection (CLND) ± lateral lymph node dissection, and their postoperative pathology was uni-PTC. This study analyzed the relevant high-risk factors of contralateral lymph node metastasis. Results: Among the 526 patients, 295 had CLNM, including 272 ipsilateral CLNM, 129 contralateral CLNM and 106 of both sides CLNM; 165 patients had LLNM including 129 ipsilateral LLNM, 18 contralateral LLNM, and 18 of both ipsilateral and contralateral LLNM. Contralateral CLNM occurred in 65 (17.8%) of 365 patients who underwent preventive CLND, and contralateral CLNM was found in 68 (42.2%) of 161 patients with therapeutic CLND. Univariate and multivariate regression analyses showed that contralateral CLNM was associated with maximum diameter of tumor ≥2 cm, multiple foci, no Hashimoto's thyroiditis, tumor invasion, number of CLNM≥6 and age <55 years (P<0.05). Maximum diameter of tumor ≥2 cm was related to contralateral LLNM (P<0.05), while lymph extracapsular extension and lymph node metastasis at tumor side were independent risk factors for contralateral CLNM and contralateral LLNM (P<0.05). Follow-up showed that 5-year overall survival (OS) rate was 97.9% and 5-year disease-free survival (DFS) rate was 97.5%. Conclusion: Contralateral CLNM is more likely to occur in patients with maximum diameter of tumor ≥2 cm, multiple foci, no Hashimoto's thyroiditis, number of CLNM ≥6, age <55 years, tumor and lymph extracapsular extension and lymph node metastasis at the cancer side. In clinical practice, bilateral CLND should be considered for patients with high-risk factors to reduce the residual recurrence of the tumor. Since metastatic rate of contralateral LLNM is relatively low, preventive contralateral lateral lymph node dissection should not be performed routinely when there are no high-risk factors mentioned above.